2004
DOI: 10.1111/j.1399-0039.2004.00312.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of the CD28/CTLA4/ICOS (CELIAC3) region in coeliac disease

Abstract: In order to extend our previous findings of genetic linkage to the CD28/CTLA4/ICOS region on chromosome 2q33 (CELIAC3) in coeliac disease (CD), we have investigated 22 genetic markers in 325 Norwegian/Swedish multiplex and simplex CD families. We found both linkage and association with several markers, primarily in the multiplex material. We observed strong linkage disequilibrium (LD) between SNPs (Single Nucleotide Polymorphisms) within an LD block delimited by MH30 and D2S72. A haplotype of this region marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 35 publications
1
31
0
Order By: Relevance
“…In contrast, the Italian case-control material showed association with several markers in the CTLA4 gene itself and throughout the CTLA4-ICOSe1 block, including the rs231775*A (CTLA4 þ 49*A) allele. This variant has previously been shown to be associated with CD in another Italian cohort 29 and in several other populations, 24,25,[30][31][32][33] as shown in Table 5c.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In contrast, the Italian case-control material showed association with several markers in the CTLA4 gene itself and throughout the CTLA4-ICOSe1 block, including the rs231775*A (CTLA4 þ 49*A) allele. This variant has previously been shown to be associated with CD in another Italian cohort 29 and in several other populations, 24,25,[30][31][32][33] as shown in Table 5c.…”
Section: Discussionmentioning
confidence: 91%
“…For the Finnish-Hungarian CD family material, the HLA-DR3-DQ2-negative IgAD patients, and for IgAD patients in general, the markers and haplotypes associated with disease risk pointed to CTLA4-ICOSe1 haplotype group 4, which also seems to carry the previously reported Scandinavian and Dutch CD risk alleles and haplotypes. 24,25 To investigate the role of polymorphisms in CTLA4-ICOS on gene expression, previously published 26 mRNA expression data of ICOS, full-length CTLA4 (flCTLA4) and soluble CTLA4 (sCTLA4) splice variants in CD4 þ T cells were re-analyzed based on the current expanded genotyping results (Table 5d; Supplementary Figure 1). Earlier, rs3087243, rs10932029 and rs10932037 genotypes were demonstrated to affect the expression of CTLA4 and ICOS.…”
Section: Ctla4-icos Locus In Celiac Disease and Igadmentioning
confidence: 99%
“…Searching for genes influencing coeliac disease Å T Naluai et al haplotypes 107,112 and some studies fail to show association. 113 -115 Other studies with negative results could remain unpublished.…”
Section: Fine-mapping and Positional Candidates On Chromosomes 5 And 19mentioning
confidence: 99%
“…A +49A/G base substitution can cause a change from threonine to alanine amino acid in the coding region of CTLA-4 (8). The CTLA-4 +6230 (rs3087243) and CTLA4 +49 SNPs have shown strong linkage disequilibrium, which have resulted in excellent combinations for haplotype analysis (9,10). Previous studies have demonstrated that the +49 SNP of CTLA-4 played a role in the development of Graves' disease (11), systemic lupus erythematous (12) and other autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%